Developing the Competencies of Public Health Volunteers for Basic Public Health Care in Remote Communities - เพชรานนท์ บวรศักดิ์; กติกาโชคสกุล ธัญญ์วรา (Journal of Health Science of Thailand, 2025)
Ethnic communities in remote areas face limitations in travel, knowledge of the Thai language, and lifestyles that conflict with medical health care principles. These factors hinder their access to proper health services from the government. A viable approach is to develop “village doctors” from within the community. These village doctors would serve as the first point of contact for basic health services and link with health officers and community hospital doctors. This study aimed to propose a learning process model for developing village doctors and connecting them with subdistrict health promoting hospitals (SHPHs). The operation methods include: (1) coordinating plans with local health units, defining desired competencies that address health needs specific to the area, and outlining the scope, content, and activities for competency development; (2) selecting village health volunteers (VHVs), focusing on those who had actively worked in the area, and exhibited leadership qualities in public health; (3) developing competencies in medical knowledge and skills, service attitudes, and photography skills to communicate health conditions, utilizing David Kolb’s Experiential Learning Theory through both onsite and online formats; (4) developing suitable health communication materials; and (5) developing mobile medical kits and management mechanisms. The study found that the active learning platform, consisting of six activities, effectively elevated regular VHVs to become village doctors, or “super VHVs,” with 27 of them in 22 communities within 10 months. These super VHVs provided services for common ailments 939 times, monitored chronic patients 190 times, screened for chronic diseases in 2,039 individuals aged 35 and above, cared for the elderly 290 times, assisted disabled persons 47 times, and promoted health through 12 community projects.